MENELISIK KURIKULUM PAI DALAM MENGHADAPI TANTANGAN PENDIDIKAN KONTEMPORER - Rasmita; Darsi (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Islamic Religious Education (PAI) faces challenges in dealing with the changing times and the demands of contemporary education. This study aims to analyze the PAI curriculum in facing the challenges of contemporary education. The research method used is a literature study by examining various sources related to the PAI curriculum and contemporary educational issues. The results of the research show that there are several aspects that need to be analyzed in developing a PAI curriculum that is relevant to the challenges of contemporary education, namely: 1) The relevance of the PAI curriculum to the needs of students and the development of the times; 2) Strengthening the spiritual dimension in the PAI curriculum to overcome moral decadence; 3) Integration of science and religion in the PAI curriculum; 4) Development of 21st century competencies such as critical thinking, creativity, communication, and collaboration; 5) Strengthening digital literacy in the PAI curriculum; and 6) Contextual learning that is relevant to the real life of students. Analysis of these aspects is expected to produce a PAI curriculum that can prepare students to face the challenges of contemporary education, so that the goals of Islamic religious education can be achieved optimally.